Comparing treatment effects in a clinical sample of patients with probable Alzheimer’s disease treated with two different cholinesterase inhibitors - Cafarra, P.; Vezzadini, G.; Capelli et al., S. (Acta Biomedica Atenei Parmensis, 2007)
Background: The aim of this study was to compare the effect of treatment with different cholinesterase inhibitors (ChEIs) on mental status and every day function in a natural outpatient clinic setting, so that this evaluation could more realistically reveal the effects which are likely to be observed in patients attending ordinary dementia clinics rather than in the context of a randomised controlled drug trial. Methods: Long term outcome of treatment with the ChEIs donepezil and rivastigmine was retrospectively evaluated in 147 patients with a clinical diagnosis of probable Alzheimer’s disease of mild to moderate level of severity who had been monitored for a period of nine months. Measures included Mini Mental State Examination, Activity of Daily Living and Instrumental Activity of Daily Living scales. Results: Response rate was similar to that of other published clinical trials on ChEIs. Patients who responded well to treatment with ChEIs better maintained their improved performance. Conclusions: Treatment with both ChEIs resulted in improved performance in those patients responding to therapy. Greater response was observed in previously untreated patients who had a shorter disease history but overall the findings in this unselected clinical sample confirmed that patients gain some benefit from intervention with ChEI treatment.